AB0098 A unique subset of rheumatoid arthritis defined by a distinct serum cytokine profile. (23rd January 2014) - Al-Mossawi, M.H.; Roy, M.; Clarke, L.; Webber, S.; Zakout, S.; Straub, R.H.; Perry, M.; Lee, M.; Kirwan, J.R.; Winfield, R.
Abstract : Background: Research into the pathogenesis of rheumatoid arthritis (RA) has been focusing on identifying disease biomarkers that can predict response to therapy. Early work identified differing levels of pro-inflammatory cytokines within a cohort of RA patients [1]. A recent study looking at the role of a modified release glucocorticoid preparation in the management of RA may have identified a distinct subgroup of patients who are resistant to therapy [2] with raised circulating levels of the cytokines TNF-α, IL-4, IL-1 receptor antagonist (IL-1ra) and IL-1β compared to treatment responders. The concept of glucocorticoid resistance in RA has been observed in other studies and across the spectrum of inflammatory disorders [3, 4]. Objectives: This study explores the the possibility of identifying a treatment resistant phenotype subset of patients with RA through peripheral serum cytokine measurements. Methods: 41 patients with RA were recruited from general rheumatology clinics in the South-West of the United Kingdom (Bristol and Plymouth). Additional exclusion criteria included active malignancy, active infection and co-existing auto-immune disease. Patient blood samples were taken in the morning to minimise diurnal cytokine variations and cytokine assays were performed using a MILLIPLEX® MAP multiplex assay kit at a commercial laboratory in Germany. Results: Results were analysed according to the number of patients who had raised serum TNF-α, IL-4, IL-1ra and IL-1β above the cohort median for each cytokine. The frequencies of the number of patients who had 0, 1, 2, 3 or all 4 cytokines raised were recorded. This revealed a biphasic distribution of patients with 16/41 patients having 3 or 4 raised cytokines versus 22/41 patients having only 1 or 0 cytokines raised. Only 3 patients had 2 raised cytokines. This is a much smaller figure than predicted, as we would expect the population to be normally distributed. The P value for the Chi squared test comparing the observed population versus the expected normal distribution was <0.0001. Conclusions: These results confirm previous observations that a distinct subset of patients with rheumatoid arthritis patients can be identified through the serum cytokine signature. Previous studies seem to imply that these patients may exhibit a glucocorticoid resistant phenotype. Further work is planned to explore the association of these two subsets of rheumatoid arthritis with various clinical characteristics. References: Ulfgren AK, et al. Interindividual and intra-articular variation of proinflammatory cytokines in patients with rheumatoid arthritis: potential implications for treatment. Ann Rheum Dis 2000;59(6):439-47. Clarke LL et al. Alleviation of morning joint stiffness by low-dose prednisone in rheumatoid arthritis is associated with circadian changes in IL-6 and cortisol. International Journal of Clinical Rheumatology 2011;6(3):273-279 doi 10.2217/ijr.11.12. Sliwinska-Stanczyk P et al. The effect of methylprednisolone on the proliferation of PBMCs obtained from steroid-sensitive and steroid-resistant rheumatoid arthritis patients. Scandinavian Journal of Rheumatology 2007;36:167-71. Barnes, P.J. & Adcock, I.M. Glucocorticoid resistance in inflammatory diseases. The Lancet 2009;373:1905–1917. Disclosure of Interest: None Declared